Enhancing Efficiency and Regulation Current in Dynamic Wireless Charging of Electric Vehicles: Phase-Shift Control Methods in Resonant Inductive Power Transfer Systems - Wissam Ayad Kiddm; S. S. Mortazavi; Mohsen Saniei; Mehdi Monadi (IEEE Access)
Wireless Power Transfer (WPT) introduces the possibility of charging electric vehicles (EVs) on a move, a concept known as Dynamic Wireless Charging (DWC). This paper proposes a solution for dynamic EV charging misalignment problems while restricting the charger current within permissible limits without any communication between the vehicle and the ground. This study aims to maximize the power transfer efficiency throughout the entire operational period of the charging device during EV motion over the charger coil, using Resonant Inductive Power Transfer (RIPT) technology. This study examined the effects of frequency and phase shifts on energy efficiency. It proposed two control methods for the primary-side current to maintain it within permissible values while considering factors such as varying load resistance and issues associated with misalignment. The simulation and practical results demonstrate that the phase-shift method effectively maintains the primary charging current within nominal limits. Additionally, it achieves higher efficiency, better power factor, and greater power transfer than the frequency control method, particularly when combined with a fuzzy controller. Using the proposed method, the transferred energy efficiency reached (88-93.5)% over the entire charging period. A prototype 40.2 W charging unit with primary and secondary coils was implemented and tested in a laboratory environment.